Burden of Cardiac Siderosis in a Thalassemia-Major Endemic Population: A Preliminary Report From Pakistan. Issue 5 (July 2016) - Alvi, Najveen; Tipoo, Fateh A.; Imran, Ahmed; Ashraf, Muhammad N.; Qidwai, Asim; Khursheed, Mohammed; Moiz, Bushra; Adil, Salman N.; Fadoo, Zehra; Altaf, Sadaf; Pennell, Dudley J.; Hasan, Babar S.
Abstract : Objective: To describe the initial experience and demographics of T2* cardiac magnetic resonance–based myocardial-iron quantification of transfusion-dependent thalassemia-major (TM) patients from Pakistan and the correlation with serum ferritin. Methods: Eligible TM patients presenting between April 2014 and April 2015 to Aga Khan University Hospital, Pakistan, for T2*CMR were included. The severity of myocardial-iron deposition was defined as follows: normal T2*>20 ms, mild-moderate T2*10 to 20 ms, and severe T2*<10 ms. Cardiac symptoms were classified using the NYHA functional classification. Echocardiographic systolic and diastolic functions were performed. Continuous variables were presented as the median (minimum-maximum value). Correlation was measured using the Spearman rank correlation. Multivariate logistic regression was used to determine factors associated with the NYHA functional class. Results: A total of 83 patients (49 male and 34 female) with TM, age 19 (5 to 45) years at presentation for T2*CMR, were reviewed. At presentation, 70% of the patients were classified as NYHA class II or worse. T2*<20 ms was observed in 62.6% of the patients, with 47% showing severe iron deposition (T2<10 ms). No correlation of T2*<20 ms ( r =−0.157, P =0.302) and T2*<10 ms ( r =−0.128, P =0.464) was observed with serum ferritin. On multivariate analysis, lower T2* values correlated with a worsening NYHA functional class. Conclusions: There is a high prevalence of severe myocardial iron load in Pakistani TM patients. Serum ferritin did not correlate with T2* values. Lower T2* was the only clinical factor associated with the NYHA functional class.